Socioeconomic Drought in a Mexican Semi-arid City: Monterrey Metropolitan Area, a Case Study - Magaña, Víctor; Herrera, Eduardo; Ábrego-Góngora, Carlos J.; Ávalos, José Antonio (Frontiers in Water, 2021)
The Monterrey Metropolitan Area (MMA) is located in northeastern Mexico in a semi-arid region. As in other areas of the world, prolonged and severe meteorological droughts are recurrent. Meteorological droughts affect the level of dam reservoirs, rivers, and groundwater (aquifers) in the region to the extent they become hydrological droughts which in turn may contribute to socioeconomic droughts. The recent dry event (2011-2013) in northern Mexico severely affected various socioeconomic sectors and may serve as an example of future climatic and hydrologic conditions in this region. Intense pressure from meteorological droughts presently exists on the water resources services of the Monterrey Metropolitan Area (MMA), one of the largest cities in Mexico. Meteorological droughts in northeastern Mexico, mostly induced by anomalously intense subsidence, frequently result in hydrological droughts and intense pressure in the water resources services of the Monterrey Metropolitan Area (MMA), one of the largest cities in Mexico. Landfalling tropical cyclones entering northeastern Mexico historically have alleviated water crises during prolonged droughts. In 2013, the rains from tropical cyclone Ingrid helped to recover water levels in the system of dam reservoirs that provides water to the MMA. However, water management is only one part of a complex socioeconomic system that must respond to the growing demands for water in a region where aquifers are already overexploited. Trends in the atmospheric circulation indicate that droughts in the region may become more severe in the coming decades. Improved water management programs and protocols should be considered in addition to closer reviews of the hydraulic infrastructure. Water transfers from one region to another should be carefully planned because solving a problem in one place may adversely affect another. The use of climate information may be critical to avoidance of water conflicts in the future.